2019
DOI: 10.1056/nejmoa1710926
|View full text |Cite
|
Sign up to set email alerts
|

Oral versus Intravenous Antibiotics for Bone and Joint Infection

Abstract: Background The management of complex orthopedic infections usually includes a prolonged course of intravenous antibiotic agents. We investigated whether oral antibiotic therapy is noninferior to intravenous antibiotic therapy for this indication. Methods We enrolled adults who were being treated for bone or joint infection at 26 U.K. centers. Within 7 days after surgery (or, if the infection was being managed without surgery, within 7 days after the start of antibiotic treatment), participants were randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
407
1
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 619 publications
(466 citation statements)
references
References 18 publications
(19 reference statements)
15
407
1
8
Order By: Relevance
“…In most of the RCTs of antibiotic treatment of antibiotics, however, the authors prescribed parenteral antibiotics followed by a switch to oral antibiotics. One non‐inferiority RCT that was published after the inclusion dates of our systematic review, and was therefore not included in the search results, randomized subjects with a variety of severe osseous and joint infections, including approximately 20% subjects with diabetic foot osteomyelitis, to treatment with an oral versus a parenteral antibiotic regimen . There were no significant differences in treatment outcomes between the two routes of therapy for the various types of infections combined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In most of the RCTs of antibiotic treatment of antibiotics, however, the authors prescribed parenteral antibiotics followed by a switch to oral antibiotics. One non‐inferiority RCT that was published after the inclusion dates of our systematic review, and was therefore not included in the search results, randomized subjects with a variety of severe osseous and joint infections, including approximately 20% subjects with diabetic foot osteomyelitis, to treatment with an oral versus a parenteral antibiotic regimen . There were no significant differences in treatment outcomes between the two routes of therapy for the various types of infections combined.…”
Section: Resultsmentioning
confidence: 99%
“…Saltoglu et al; Lipsky et al; Lauf et al; Grayson et al; Erstad et al; Lipsky et al; Lipsky et al; Lipsky et al; Lázaro‐Martínez et al; Ulcay et al; Tone et al, Li et al…”
Section: Resultsunclassified
“…An ongoing large, multicenter US trial (VA INTREPID) is examining the role of rifampin in treating DFO . Several case series, and a recent large RCT, have shown that oral antibiotic therapy (usually after at least a few days of intravenous therapy) is as effective as, safer, and less expensive than intravenous therapy for complex bone and joint infection (including DFO) …”
Section: Treatmentmentioning
confidence: 99%
“…We think clinicians can prescribe initial therapy by the oral route in care- shown that oral antibiotic therapy (usually after at least a few days of intravenous therapy) is as effective as, safer, and less expensive than intravenous therapy for complex bone and joint infection (including DFO). 157 The recommended duration of treatment for osteomyelitis has traditionally been 4 to 6 weeks, but this is based mostly on animal models and clinical experience. Some studies of DFO (and other types of osteomyelitis) have shown that therapy for longer than 6 weeks offers no additional benefit, 158 and based mostly on theoretical considerations, treatment for just 1 to 2 weeks (or less) should be sufficient for patients in whom all infected bone has been resected.…”
Section: Rationalementioning
confidence: 99%
“…This is especially the case with orally administered β‐lactams whose bioavailability and doses are much lower than their IV counterparts . However, studies showed that PO antibiotics are as effective as IV antibiotics for other difficult to treat infections including left‐sided endocarditis and bone‐joint infections …”
mentioning
confidence: 99%